A bromeliad species reveals invasive ant presence in urban areas of French Guiana. (November 2015) - Talaga, Stanislas; Delabie, Jacques H.C.; Dézerald, Olivier; Salas-Lopez, Alex; Petitclerc, Frédéric; Leroy, Céline; Hérault, Bruno; Céréghino, Régis; Dejean, Alain
Highlights: The tank bromeliad, Aechmea aquilega, shelters several non-specific ant species. Four invasive species destructured the ant community in an urban area. Urban ants were baited on the ground, on trees and on trees bearing A. aquilega . Eleven invasive ants were noted in total, five of them on trees bearing A. aquilega . A bootstrap simulation showed that A. aquilega concentrates invasive ants. Abstract: Tank bromeliads, frequently associated with ants, are considered 'biodiversity amplifiers' for both aquatic and terrestrial organisms, and thus have a high ecological value. The focal species of this study, Aechmea aquilega, sheltered the colonies of 12 ant species in a Guianese rural habitat where Odontomachus haematodus, associated with 60% of these plants, was the most frequent. Unexpectedly, the ant species richness was higher in a compared urban habitat with 21 species, but two synanthropic and four invasive ants were noted among them. Consequently, we conducted baiting surveys (on the ground, on trees and on trees bearing A. aquilega ) as well as complementary surveys using different sampling modes in urban areas to test if A. aquilega is a surrogate revealing the presence of certain invasive ants. During the baiting survey, we recorded four Neotropical and eight introduced invasive ants out of a total of 69 species. Of these 12 invasive species, five were noted by baiting A. aquilega (including two only noted in this way). A bootstrap simulation permitted us to conclude that A. aquilega significantly concentrates certain species of invasive ants. This was confirmed by complementary surveys, where we did not record further species. We conclude that baiting on trees bearing large epiphytes in human-modified, Neotropical areas is a relevant complement to the early detection of invasive ants.